2014
DOI: 10.4028/www.scientific.net/amr.1058.240
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Sputtering Power on the Structural, Morphological and Optical Properties of ZnSe Thin Films Deposited by R.F Magnetron Sputtering

Abstract: By creatively using R.F Magnetic sputtering technique , we have successfully prepared ZnSe polycrystalline thin films on glass substrates..The effect of different sputtering powers on the structural, morphological and optical properties of the as-deposited films were studied. The films were characterized by using X-ray diffraction, UV-VIS spectrometer ,scanning electrical microscope ,etc. The results indicate that :Under the pressure of o.8pa,with the diverse sputtering power varying from 60w to 100w,the inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
0
4
1
Order By: Relevance
“…These films are of better morphology than the ones we reported here. The estimated direct allowed energy band gap of the films grown onto glass substrates by the magnetron sputtering technique being 2.48 eV is larger than [37] those we achieved by the thermal evaporation technique. On the other hand, cubic ZnSe thin films of thickness of 100 nm coated onto indium tin oxide (ITO) substrates by the thermal evaporation technique exhibited larger lattice parameters, smaller crystallite sizes and wider energy band gaps [38].…”
Section: Resultscontrasting
confidence: 62%
See 1 more Smart Citation
“…These films are of better morphology than the ones we reported here. The estimated direct allowed energy band gap of the films grown onto glass substrates by the magnetron sputtering technique being 2.48 eV is larger than [37] those we achieved by the thermal evaporation technique. On the other hand, cubic ZnSe thin films of thickness of 100 nm coated onto indium tin oxide (ITO) substrates by the thermal evaporation technique exhibited larger lattice parameters, smaller crystallite sizes and wider energy band gaps [38].…”
Section: Resultscontrasting
confidence: 62%
“…It is interesting to compare the structural and optical properties of ZnSe thin films grown by the thermal evaporation technique with films grown by the RF magnetron sputtering technique [37]. These films are observed to exhibit cubic structure with lattice parameters of 5.66 Å.…”
Section: Resultsmentioning
confidence: 99%
“…The XRD results revealed that a low RF power value of 100 W could not initiate crystallization or the crystal lattice orientation at room temperature since the surface mobility of the particles on the substrate and the kinetic energy of the sputtered particles are low at this low value of RF power [26]. As a result, the sputtered particles cannot arrive at low energy lattice positions, leading to the formation of ZnS films with less ordering or an amorphous nature [27]. An increase in the RF power to 120 W gives sufficient energy to the ad-atoms, increasing their mobility to the low energy lattice positions and leading to crystallization of the film.…”
Section: Fig 1(a)-(d) Xrd Patterns Of the Zns Films Deposited On Quamentioning
confidence: 99%
“…An increase in the RF power to 120 W gives sufficient energy to the ad-atoms, increasing their mobility to the low energy lattice positions and leading to crystallization of the film. The increase in the RF power to 150 W again increases the ad-atom mobility and provides enough diffusion activation energy to occupy the most beneficial lattice positions in an ordered manner, leading to atomic rearrangement and good crystallization of the film [27,28]. Increasing the sputtering power beyond 150 W provides excess kinetic energy to the sputtered particles, which increases the collisions and atomic scattering.…”
Section: Fig 1(a)-(d) Xrd Patterns Of the Zns Films Deposited On Quamentioning
confidence: 99%
See 1 more Smart Citation